PERANCANGAN GAME FPP MOUNTAIN CLIMBING LIFE SIMULATION MENGGUNAKAN METODE GDLC - Micheal, Micheal; Simanjuntak, Fredian (Computer Based Information System Journal, 2024)
This research aims to design a life simulation game with the theme "FPP Mountain Climbing Life Simulation" as an entertainment tool and a means of learning about rock climbing activities. Through the Research & Development process, the author conducted in-depth research to identify the needs and requirements in designing this game. The research results indicate that this game can be an entertainment tool that combines the realism of rock climbing with life simulation game elements, allowing players to experience rock climbing virtually. Additionally, a qualitative expert-interview method was used to gain deeper insights into rock climbing by interviewing experts and experienced individuals in the activity. The Game Development Life Cycle (GDLC) method was used in the Development phase to design and develop the game. "FPP Mountain Climbing Life Simulation" has the potential to be an effective learning tool for teaching techniques, preparations, and necessary steps in rock climbing, as well as the importance of safety. Recommendations include further development of the game, providing more detailed guides, promoting the game to the climbing community, and conducting further research to measure the game's effectiveness as a learning tool.